Indicadores sociodemográficos, clínicos e fonoaudiológicos para decanulação em pacientes adultos traqueostomizados - Margaret Mendonça Diniz da Côrte (2018)
Objective: To identify the important sociodemographic, clinical and phonoaudiological indicators for the success in the decannulation of adult tracheostomized patients, elaborating a protocol of decannulation. Methods: This is a retrospective, observational, analytical study, with a crosssectional design, in which sociodemographic, clinical and speech-language data were collected from the medical records of all adult decannulated or nondecannulated tracheostomized patients, over 18 years of age, with a score greater than 8 on the Glasgow Coma Scale (ECG), attended by the Speech-Language Pathology and Audiology Service of the Governador Israel Pinheiro Hospital (HGIP), from June 2014 to December 2016. Data were collected: sociodemographic data - age and sex, clinicians - baseline disease, time of orotracheal intubation, use of mechanical ventilation, level of consciousness, effective cough, ability to remove secretions, absence of abundant respiratory secretions, active infections, use of oxygen therapy and exchange of plastic cannula for metal and phonoaudiology - classification of swallowing in dysphagia or functional deglutition, vocal changes, spontaneous swallowing of saliva, oral diet, Blue Dye Test result, use of a speech valve, and deflated cuff tolerance. Data were submitted to statistical analysis, and descriptive analyzes of all study variables and bivariate and multivariate inferential analysis were performed through multivariate multiple logistic regression analysis. Results: The sample consisted of 189 tracheostomized patients, with a mean age of 70.9 years (DP=11,9), predominantly male and mostly resident in the Belo Horizonte. Some speech-language variables were associated with the success of decannulation, with a greater proportion of patients who had decannulated among those with functional swallowing (p <0.001), absence of vocal changes (p <0.001), spontaneous swallowing of saliva (p <0.001), higher level of consciousness (p <0.001), oral diet (p <0.001) p <0.001), effective cough (p <0.001), ability to remove secretions (p <0.001), absence of abundant secretions (p <0.001), use of a speech valve (p <0.001), tolerance to the deflated cuff (P <0.001), exchange of plastic cannula for metal cannula (p <0.001), had no active infections (p <0.001), and did not use oxygen therapy during occlusion (p <0.001). Conclusion: The present study demonstrated that there are indicators related to decannulation that can be considered predictive of success in the process. The variables considered determinant are the absence of abundant secretions, the ability to remove secretions and the occlusion time of the tracheostomy.